2016
DOI: 10.1016/j.molp.2015.10.011
|View full text |Cite
|
Sign up to set email alerts
|

MSH1 Is a Plant Organellar DNA Binding and Thylakoid Protein under Precise Spatial Regulation to Alter Development

Abstract: As metabolic centers, plant organelles participate in maintenance, defense, and signaling. MSH1 is a plant-specific protein involved in organellar genome stability in mitochondria and plastids. Plastid depletion of MSH1 causes heritable, non-genetic changes in development and DNA methylation. We investigated the msh1 phenotype using hemi-complementation mutants and transgene-null segregants from RNAi suppression lines to sub-compartmentalize MSH1 effects. We show that MSH1 expression is spatially regulated, sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
92
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(98 citation statements)
references
References 62 publications
6
92
0
Order By: Relevance
“…In Arabidopsis msh1 T-DNA insertion lines, phenotypes include leaf variegation, reduced growth rate, delayed flowering, extended juvenility, altered floral morphology, aerial rosettes and enhanced secondary growth (Xu et al, 2012). These mutants also show tolerance to heat, high light and drought stress (Shedge et al, 2010;Virdi et al, 2016;Xu et al, 2011). These pleiotropic phenotypes are largely attributed to depletion of MSH1 from plastids, evidenced by hemi-complementation analysis (Xu et al, 2012), and the msh1-triggered plastid changes condition genomewide methylome repatterning (Virdi et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In Arabidopsis msh1 T-DNA insertion lines, phenotypes include leaf variegation, reduced growth rate, delayed flowering, extended juvenility, altered floral morphology, aerial rosettes and enhanced secondary growth (Xu et al, 2012). These mutants also show tolerance to heat, high light and drought stress (Shedge et al, 2010;Virdi et al, 2016;Xu et al, 2011). These pleiotropic phenotypes are largely attributed to depletion of MSH1 from plastids, evidenced by hemi-complementation analysis (Xu et al, 2012), and the msh1-triggered plastid changes condition genomewide methylome repatterning (Virdi et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that tissue-specific gene expression analyses distinguishing epidermal and mesophyll tissues were never reported and that the results in all studies to date, thus, represent a mixture of both cell types. This is critical with respect to the notion that recent studies suggest a specific sensor function for epidermal chloroplasts (Virdi et al, 2015, 2016). Targeted research on this special type of chloroplasts will be required in order to understand their detailed physiological function.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that msh1 mutants are more tolerant to drought, high light, and heat stress (Shedge et al, 2010; Virdi et al, 2016; Xu et al, 2011). We tested for other abiotic stress effects, focusing first on salt and freezing temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Arabidopsis msh1 mutants display a range of altered phenotypes that include variegation, dwarfing, delayed maturity transition, delayed flowering, and partial male sterility (Xu et al, 2011). The msh1 mutants display higher tolerance to heat, high light, and drought stress (Shedge et al, 2010; Virdi et al, 2016; Xu et al, 2011), particularly in individuals showing stronger developmental phenotypes. MSH1 phenotypes are conserved between monocots and eudicots.…”
Section: Introductionmentioning
confidence: 99%